Growth Temperature Influences Postharvest Quality and Cold Tolerance of Green Harvested Dwarf Tomatoes During Storage - Affandi, Fahrizal Yusuf; Pijnenburg, Charlotte; Verdonk, Julian C.; Woltering, Ernst J.; Schouten, Rob E. (Frontiers in Sustainable Food Systems, 2022)
Effect of cultivation temperature during the phase of flowering and fruit development on tomato quality was investigated. Plants of two dwarf tomato cultivars “Ponchi Re” and “Tarzan,” were subjected to three different growth temperatures: 16, 22, or 28°C, starting at the flowering phase. Mature green fruit was harvested and subjected to shelf life at 20°C for 20 days or first stored at 4°C for 15 days, and then placed under shelf life conditions. Fruit quality was determined through red color development, soluble solid content (SSC), softening, weight loss, and cold tolerance. Higher cultivation temperature increased development and production of fruit. Deviation from the 22°C growth temperature led to increased soluble solid content in both cultivars, and smaller fruit diameter in “Tarzan.” Fruit grown at lower temperature had delayed color development during shelf life, and this was further delayed by prior cold storage. “Tarzan” showed more chilling injury (CI) symptoms than “Ponchi Re.” In our experiment, SSC can be manipulated by modulating cultivation temperature, but that it is not associated with CI tolerance. Delayed color formation at the lowest growth temperature observed in “Ponchi Re” tomatoes could be resulted in lower lycopene levels leads to lower ROS scavenging capacity. For “Tarzan” tomatoes, higher firmness at harvest, less softening, and lower weight loss during cold storage in fruit from the lowest cultivation temperature might positively correlated with increased membrane integrity, resulting in increased CI tolerance. This indicates that CI incidence depends on growth temperature and is cultivar dependent in dwarf tomato fruit.